1986
DOI: 10.1021/i100023a019
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of ethanol from a molecular sieve by using dielectric heating

Abstract: Application of electrical energy of the appropriate frequency dielectrically heats the ethanol without heating the molecular sieve. This causes the ethanol to be driven from the pores of the molecular sieve by a combination of vaporization and expulsion, resulting in a very rapid energy-efficient process. The carrier gas used to remove the desorbed chemical (ethanol) from the column is chosen to leave the molecular sieve in the best condition for the next cycle of sorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…According to this, E a for MMA polymerization in the MWF is different and significantly lower than E a under the conventional polymerization conditions. The power of the MWF per unit volume which is absorbed by reaction system under the influence of the MWF due to the dielectric losses is given in the following equation 17,18 :…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this, E a for MMA polymerization in the MWF is different and significantly lower than E a under the conventional polymerization conditions. The power of the MWF per unit volume which is absorbed by reaction system under the influence of the MWF due to the dielectric losses is given in the following equation 17,18 :…”
Section: Resultsmentioning
confidence: 99%
“…According to this, E a for MMA polymerization in the MWF is different and significantly lower than E a under the conventional polymerization conditions. The power of the MWF per unit volume which is absorbed by reaction system under the influence of the MWF due to the dielectric losses is given in the following equation 17,18 : S a;a ¼ 55:63 Â 10 À12 fU 2 e 00 r (12) where f is the frequency (Hz), U is the local field intensity (V/m), and e 00 r is the imaginary part of dielectric constant.…”
Section: Resultsmentioning
confidence: 99%
“…Burkholder et al 1 found that applying microwave energy enhances the desorption of ethanol from silicalite because it selectively heats the ethanol without heating the adsorbent. Furthermore, the researchers recognized the possibility for using MW regeneration to facilitate solvent recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that regeneration conditions and heating method can impact heel build-up on activated carbon. , Conductive heating, hot gas purging, and steam heating are typically used to regenerate adsorbents. Drawbacks associated with these techniques include long duration, high energy consumption due to heat loss (to surrounding equipment, adsorbent, and concentrated VOC gas stream), and potential changes to the adsorbent’s physical and chemical properties. …”
Section: Introductionmentioning
confidence: 99%